Assembly of The Mitochondrial Complex I Assembly Complex Suggests a Regulatory Role for Deflavination. Issue 9 (12th January 2021) - Giachin, Gabriele; Jessop, Matthew; Bouverot, Romain; Acajjaoui, Samira; Saïdi, Melissa; Chretien, Anaïs; Bacia‐Verloop, Maria; Signor, Luca; Mas, Philippe J.; Favier, Adrien; Borel Meneroud, Eve; Hons, Michael; et al.
Abstract: Fatty acid β‐oxidation (FAO) and oxidative phosphorylation (OXPHOS) are mitochondrial redox processes that generate ATP. The biogenesis of the respiratory Complex I, a 1 MDa multiprotein complex that is responsible for initiating OXPHOS, is mediated by assembly factors including the mitochondrial complex I assembly (MCIA) complex. However, the organisation and the role of the MCIA complex are still unclear. Here we show that ECSIT functions as the bridging node of the MCIA core complex. Furthermore, cryo‐electron microscopy together with biochemical and biophysical experiments reveal that the C‐terminal domain of ECSIT directly binds to the vestigial dehydrogenase domain of the FAO enzyme ACAD9 and induces its deflavination, switching ACAD9 from its role in FAO to an MCIA factor. These findings provide the structural basis for the MCIA complex architecture and suggest a unique molecular mechanism for coordinating the regulation of the FAO and OXPHOS pathways to ensure an efficient energy production. Abstract : Fatty acid oxidation (FAO) and oxidative phosphorylation (OXPHOS) are key mitochondrial pathways for cellular energetics. However, the crosstalk between them is unclear. We show that the molecular architecture of the mitochondrial Complex I assembly (MCIA) complex, required for Complex I biogenesis and thereby for activation of OXPHOS, implies an allosteric deflavination mechanism that shuts down FAO.